Effect of strength training programs on shoulder and scapular muscle among elite swimmers - Alemi, Behzad; Tengku Kamalden, Tengku Fadilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
On previous Olympic Games, swimming was one of the most popular events and it has encouraged improvement in conditioning, technical advances, and the use of sophisticated training equipment, but escalations in the level of competition and training have been allied to a concurrent rise in shoulder damages. Competitive swimmers exercise almost every day and swim on average 12000 meters each day, approximately 16000 times of shoulder rotation. Strength imbalances of the shoulder musculature and shoulder pain are suggestively correlated in swimming athletes and Shoulder instability can lead to pain, impingement, and decreased functioning in overhead athletes. Literatures have tried to examine whether changes occur in shoulder girdle muscle performance and strength by using the appropriate strengthening exercise. This study reviews those previous studies intervention and explains the result of each exercise protocols on rotator cuff muscles. All of previous studies commonly suggested that exercise interventions might encourage the proper posture of swimmers. They are recommending that their program had a protective effect pain but so far few studies have planned a prevention program design specifically for swimmers shoulder that addresses the weaknesses and changed movement pattern of swimmers.